Rapid determination of mixed soil and biochar properties using a shortwave near infrared spectroscopy approach. Issue 1 (February 2021) - Darusman, D; Juwita, I R; Munawar, A A; Zainabun, Z; Zulfahrizal, Z
Abstract: Presented study aimed to apply the near infrared spectroscopy approach in determining some related properties of soil mixed by biochars. Spectra data of soil samples were acquired using a self-developed NIRS instrument (PSD NIRS i16) in shortwave near infrared (SW-NIRS) range from 1000 to 1750 nm with optical gain 4x and co-added of 32 scans per acquisitions. Spectra data were corrected and enhanced using mean centering and peak normalization. Multivariate analysis namely principal component regression (PCR) were employed to develop NIRS based models followed with leverage validation. The results showed that mixed soil samples with biochar properties (K and N) can be determined simultaneously with maximum correlation coefficient are 0.86 and 0.77 for K and N respectively. Based on this obtained performance, it may conclude that SW-NIRS approach can be applied to determine related properties of mixed soil biochar samples rapidly.